Tutorial for Internet Chat Room Meetings. - McClintock, Paul (Parliamentary Journal, 2009)
Part of a special issue on “e-meetings.” The writer presents a tutorial for Internet chat-room meetings. He provides information on accessing the chat-room meeting online, posting messages during the meeting, and leaving the meeting when finished. He also supplies a sample transcript of a chat-room meeting.